Correction: TGM2, HMGA2, FXYD3, and LGALS4 genes as biomarkers in acquired oxaliplatin resistance of human colorectal cancer: A systems biology approach. - Tayebeh Cheraghi-Shavi; Razieh Jalal; Zarrin Minuchehr; Frouzandeh Mahjoubi (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0289535.].